2014
DOI: 10.1002/2013ja019619
|View full text |Cite
|
Sign up to set email alerts
|

Development of intermediate scale structure near the peak of the F region within an equatorial plasma bubble

Abstract: Scintillation observations are used to study the evolution of intermediate scale (~100 m-few kilometers) irregularities through growth of the Rayleigh-Taylor (R-T) instability on the bottom side of the post-sunset equatorial F region during magnetically quiet periods. Amplitude scintillations on a VHF signal from a geostationary satellite, recorded by spaced receivers at an equatorial station, are used to compute as a function of local time: (1) the coherence scale length for spatial variations of intensity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 31 publications
1
30
2
Order By: Relevance
“…At the same time above the F peak at the equatorial station the irregularity spectrum is shallower as small‐scale irregularity develops there before midnight [ Bhattacharyya et al , ]. These irregularities map down to off equatorial stations.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time above the F peak at the equatorial station the irregularity spectrum is shallower as small‐scale irregularity develops there before midnight [ Bhattacharyya et al , ]. These irregularities map down to off equatorial stations.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, as the large-scale bubbles map down along geomagnetic field lines to off-equatorial latitudes, the spectrum of the intermediate-scale irregularities within the bubbles tends to become shallower near the F-region peak. This factor, based on the recent study of Bhattacharyya et al (2017), also contributes to the strong L-band scintillations observed near the crest of the EIA, particularly in years of high solar activity and during the December solstice months in the longitude of Cachoeira Paulista. Figure 1 also shows that the occurrence of scintillation started to subside with the decline in solar activity.…”
Section: Ionospheric Scintillation Climatologymentioning
confidence: 92%
“…Once the spatial distribution and strength of the scintillations are dominated by the background electron density, the most intense scintillations are expected to occur around 15-20 • from the magnetic equator at latitudes of the crests of the EIA. Moreover, the latitudinal variation in the intermediate-scale length (from hundreds of meters to a few kilometers) irregularity spectrum within a plasma bubble may also contribute to strong scintillations near the crests of the EIA (Bhattacharyya et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in Bhattacharyya et al . [], these results of Retterer [] indicate that prior to 22 h local time (LT), the power spectrum of VTEC fluctuations is shallowest in the EIA crest region at a geomagnetic latitude of ~16°. Since the maximum contribution to VTEC at any location comes from the F layer peak region, it could be concluded that for magnetic east‐west scale sizes down to 10 km, the equatorial F layer peak was less structured than that in the EIA crest region prior to 22 LT.…”
Section: Introductionmentioning
confidence: 99%